The Experiences of Women in The Perinatal Period Regarding Maternal Health Services: A Qualitative Study During The Covıd-19 Pandemic - Gözde Gökçe İşbir; Meltem Aydın Beşen (Atatürk University, 2024)
Objective: This research was conducted to determine the experiences of women in the perinatal period regarding maternal health services during the COVID-19 pandemic.Methods: This is a qualitative descriptive study. The study included 19 women who were in the perinatal period during the pandemic. Data were collected using semi-structured interview questions. Results: In this study, data obtained were divided into three themes: first- experiences toward changing maternal health services, second - results of lack of maternal health services, and third - suggestions to facilitate the accessibility of maternal health services. Conclusion: Access to maternal health services of women in the perinatal period during the pandemic should be evaluated and access to services should be ensured by developing and implementing new strategies with the contribution of community midwives while addressing situations that prevent access to these services.